Increasing The Efficiency of Solar Cells (Eurasian Scientific Herald, 2022)
On purpose increase efficiency of solar elements, it has been investigated process of ionic implantation influencing the big number of the interconnected coefficients, most important of which is target orientation, a grade, initial energy and a corner of falling of primary particles.